2018
DOI: 10.1080/08927014.2018.1439935
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial sonodynamic and photodynamic therapies againstCandida albicans

Abstract: Candida albicans biofilms exhibit unique characteristics and are highly resistant to antifungal agents. Antimicrobial photodynamic therapy (aPDT) is an alternative treatment limited to treating superficial infections due to the poor light penetration. In this manuscript, the antifungal properties of sonodynamic therapy (SDT) were assessed. SDT uses ultrasound instead of light, enabling the treatment of deeper infections. Planktonic cells and biofilms of C. albicans were treated with aPDT or SDT, in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…Presently, the most acceptable mechanism relies on ROS production which causes apoptosis [142]. An alternative theory advocates that the elevated temperatures lead to thermal destruction and might also result in the generation of free radicals directly from the sensitizers [140], with ROS being successively formed in an acoustic cavitation phenomenon-a similar approach to a PDT type I reaction [143]. When compared to aPDT, SDT's main advantage is that ultrasound propagates deeper than light, and therefore may be used to treat diseases mediated by complex and dense biofilms.…”
Section: Sonodynamic Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Presently, the most acceptable mechanism relies on ROS production which causes apoptosis [142]. An alternative theory advocates that the elevated temperatures lead to thermal destruction and might also result in the generation of free radicals directly from the sensitizers [140], with ROS being successively formed in an acoustic cavitation phenomenon-a similar approach to a PDT type I reaction [143]. When compared to aPDT, SDT's main advantage is that ultrasound propagates deeper than light, and therefore may be used to treat diseases mediated by complex and dense biofilms.…”
Section: Sonodynamic Therapymentioning
confidence: 99%
“…When compared to aPDT, SDT's main advantage is that ultrasound propagates deeper than light, and therefore may be used to treat diseases mediated by complex and dense biofilms. Moreover, SDT may facilitate the generation of transient pores in the biofilm matrix, enabling a greater diffusion of PSs, SSs, and light [143], or as a complement to aPDT [142] since the main advantage of SDT over aPDT is that ultrasound can be tightly focused with penetration in soft tissue up to several tens of centimeters.…”
Section: Sonodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Alves et al have recently reported on effective destruction of Candida albicans by photodithazine and RB in the dark under the ultrasonic excitation. A significant synergistic effect of the combination between PDT and SACT for combatting C. albicans biofilms was also found [36]. Figure 2 demonstrates the effect of ultrasonic activation that we showed on the antibacterial activity of two PSs-RB (Figure 2a) and MB (Figure 2b)-against S. aureus compared to photodynamic activation.…”
Section: Sonodynamic Excitation Of Photosensitizersmentioning
confidence: 53%
“…It was found that some well-known PSs also have sonosensitizing properties. Among them are porphyrins [35], RB [36,37], chlorin e6 derivative, photodithazine [36], and curcumin [38]. Several studies found sonodynamic therapy (SDT) to be the promising treatment in various forms of cancerous tumors [39][40][41][42][43].…”
Section: Sonodynamic Excitation Of Photosensitizersmentioning
confidence: 99%